Thiophanate methyl 45% + Pyraclostrobin 5% FS: A new molecule for potato tubers treatment against black scurf disease caused by Rhizoctonia solani - Lal, Mehi; Yadav, Saurabh; Chand, Subhash (Indian Journal of Plant Protection, 2020)
Black scurf of potato caused by Rhizoctonia solani is one of the most important limiting factors for potato production in India and worldwide. Field experiment was conducted using new molecule: thiophanate methyl 45% + pyraclostrobin 5% FS during two consecutive years (2012-2014) for the management of black scurf disease of potato. It was evaluated at four doses i.e., 10.0, 12.0, 16.0 and 20.0 ml per 100 kg tubers for bioeffcacy and two doses (20.0 and 40.0 ml/100 kg tubers) for phytotoxicity. The results revealed that thiophanate methyl 45% + pyraclostrobin 5% FS @ 20.0 ml/100 kg seed was highly effective and resulted in reduction of disease incidence (83.7% during 2012-13 and 67.5% during 2013-14) and disease severity (82.6% in 2012-13 and 60.4% in 2013-14) with higher yield followed by 16.0 ml/100 kg seed. The percentage of plant emergence was > 95% at different doses of the fungicide. No adverse effect on emergence (%), and phytotoxicity was observed when the combination product was tested at 20.0 and 40.0 ml/100 kg tubers.